2016
DOI: 10.1016/j.rbmo.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Maternal physical and sedentary activities in relation to reproductive outcomes following IVF

Abstract: Physical activity could benefit reproductive function through its ability to regulate energy balance and improve insulin sensitivity, but its association with IVF outcomes remains unclear. The aim of this study was to evaluate whether pre-treatment physical and sedentary activity is associated with outcomes of IVF. The Environment and Reproductive Health Study is an ongoing prospective cohort study that enrols subfertile couples at Massachusetts General Hospital Fertility Center. Time spent in physical and sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 25 publications
5
32
0
1
Order By: Relevance
“…In line with other studies, we did not confirm a significant association between physical inactivity and fertility in women [17,26]. However, it appears that the relationship between PA and fertility may differ according to BMI [17].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In line with other studies, we did not confirm a significant association between physical inactivity and fertility in women [17,26]. However, it appears that the relationship between PA and fertility may differ according to BMI [17].…”
Section: Discussionsupporting
confidence: 83%
“…Subgroups of women exercising under 15 min and over 60 min per session had a higher frequency of infertility than women between 16 and 60 min duration [21]. PA was not related to fertility status among women in our study, likely due to a lack of power; however, it has been shown that 1.5 h or more of aerobic PA per week resulted in a higher likelihood of live birth in women during IVF compared to inactive women [17]. As it has been observed in men, total PA level (in MET-min/week) may not be the variable most highly associated with fertility status, while PA parameters such as duration, intensity, frequency, and type of exercise could be instead.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations